Efektivitas Sistem Pengendalian Manajemen Terhadap Kualitas Laporan Keuangan PT Unilever Indonesia Tbk (2022-2024) - Fanya Rosyidur Rohmah Salsabila; Adelia Ayuningtias; Salsabil Morelza; Nurul Hidayah (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2026)
ABSTRACT Financial reports, the final result of the accounting process, present information about an entity's financial performance over a specific period. This study aims to analyze the effectiveness of the management control system in improving the quality of PT Unilever Indonesia Tbk's financial reports during the 2022-2024 period. This study uses a quantitative descriptive method with research data obtained from the company's annual financial reports. The analysis is conducted by measuring financial ratios consisting of liquidity, solvency, profitability, and activity ratios. These ratios are used to illustrate the extent to which the management control system is implemented in managing and maintaining the quality of financial reports. The results show that the liquidity ratio tends to decline, requiring stronger working capital management. The solvency ratio indicates the company's high level of dependence on debt-based funding, necessitating capital structure control to maintain financial risk. While the profitability ratio shows a downward trend, the company was still able to generate profits during the period. The activity ratio also indicates a decline in asset utilization efficiency, necessitating improved operational control and more optimal asset utilization. These findings confirm that the management control system at PT Unilever Indonesia Tbk is operating optimally, but strengthening of planning, monitoring, and performance evaluation is needed to maintain and improve the quality of financial reporting